Preparations and biomedical applications of magnetic nanoparticles and nanocomposites - Md. Eaqub, Ali; Md. Fazlul, Bari; Mohd Noor, Ahmad (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.